Meningkatkan Keberfungsian Sosial Orang Dengan Gangguan Jiwa (ODGJ) Melalui Terapi Kolaboratif Terintegrasi (TKT) - Siti Nurrahmania Apriliani; Ati Kusmawati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Social functioning is a condition in which individuals, families, groups and communities are able to fulfill their basic needs and rights, carry out their social duties and roles, and overcome problems in their lives. However, there are still many people who cannot carry out their social functions properly. One of them is a person with mental disorders (ODGJ). Mental disorder is a psychological disorder that occurs in a person. Therefore, to improve the social functioning of ODGJ, it is necessary to implement social rehabilitation. One of them is by carrying out an activity called integrated collaborative therapy.The research objective is to find out the increaseSocial Functioning of People with Mental Disorders (ODGJ) Through Integrated Collaborative Therapy (TKT). The method used in this research is descriptive qualitative. Informants in this study totaled 6 people consisting of 1 PJLP Social Worker, 1 PJLP, 1 ASN Social Worker, and 3 WBS using the techniquepurposive sampling. People with Mental Disorders (ODGJ) at the Bina Laras Harapan Sentosa 3 Social Institution receive assistance in the form of social development activities through the implementation of collaborative therapy activities integrated with reality-oriented group activity therapy. The implementation of this therapy has a considerable and positive influence on the social functioning of people with mental disorders. This can be seen from the fulfillment of 3 aspects of social functioning by the socially assisted members of PSBL HS 3. In addition, WBS cancan communicate well, be more focused, have ethics and initiative, have new skills, be adaptable, and be able to express opinions.